2007
DOI: 10.1038/sj.jcbfm.9600517
|View full text |Cite
|
Sign up to set email alerts
|

The Nitrone Disodium 2,4-Sulphophenyl-N-Tert-Butylnitrone is Without Cytoprotective Effect on Sodium Nitroprusside-Induced Cell Death in N1E-115 Neuroblastoma Cells in vitro

Abstract: Disodium 2,4-sulphophenyl-N-tert-butylnitrone (NXY-059) is a novel free radical-trapping compound that is neuroprotective in both rodent and primate models of acute ischaemic stroke. Neuroprotection in vitro by NXY-059 has not been reported previously, and we have now investigated whether such an effect can be detected using a simple cell culture model of neurotoxicity. Neuron-like cells of the neuroblastoma-derived clonal cell line N1E-115 were exposed to the free radical-generating agent sodium nitroprusside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…In contrast, karyotypic abnormalities were dramatically increased in frequency and severity when CDCs were cultured in 20% O 2 with either of two antioxidant cocktails: a proprietary antioxidant supplement for cell culture (product A1345, Sigma-Aldrich, 1000-fold dilution; Antioxidant A), or a homemade antioxidant mixture [16] (L-ascorbate, L-glutathione, and α Tocopherol acetate, each 100 μM; Antioxidant B) (Figure 1, Supporting information Table 2). Among the 12 samples of CDCs cultured with Antioxidant A or B, 8 and 6 samples included 46 and 49 cells with genomic alterations, respectively (p<0.001 vs 20% O 2 culture by chi-square test, Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, karyotypic abnormalities were dramatically increased in frequency and severity when CDCs were cultured in 20% O 2 with either of two antioxidant cocktails: a proprietary antioxidant supplement for cell culture (product A1345, Sigma-Aldrich, 1000-fold dilution; Antioxidant A), or a homemade antioxidant mixture [16] (L-ascorbate, L-glutathione, and α Tocopherol acetate, each 100 μM; Antioxidant B) (Figure 1, Supporting information Table 2). Among the 12 samples of CDCs cultured with Antioxidant A or B, 8 and 6 samples included 46 and 49 cells with genomic alterations, respectively (p<0.001 vs 20% O 2 culture by chi-square test, Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, NXY-059 has been suggested to exert its effect in the vascular part of the neurovascular unit (Marklund et al, 2001d). Endothelial cells are proposed to be important generators of ROS (Fisher et al, 2006;Hainsworth et al, 2008;Kuroda et al, 1999), and the cerebrovascular endothelium is also exposed to high oxygen tension and free radical forming neutrophils and platelets (Kondo et al, 1996). The finding that S-PBN treatment increases blood flow in the injured cortex and hippocampus after FPI in rats (Kontos and Povlishock, 1986;Siesjo, 1992a,b) supports the notion that the nitrones affect the microvasculature after TBI.…”
Section: Mechanisms Of Neuroprotectionmentioning
confidence: 98%
“…NXY-059 may also act at the microvascular level in stroke to produce neuroprotection (Marklund et al, 2001d). Since treatment with NXY-059 resulted in marked neuroprotective actions following cerebral ischemia in rats (Hainsworth et al, 2008) and primates (Kuroda et al, 1999;Sydserff et al, 2002) despite a very limited BBB penetration following intravenous administration (Marshall et al, 2003b).…”
Section: Nitrone Radical Scavenger Concept In Acute Brain Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…They stated that NXY-059 maintained Akt activation and inhibited cytochrome c release after ischaemia and that it may interact directly with penumbral neurons or interact with the endothelial cell to alter signal transduction pathways. Subsequent work has indicated that NXY-059 has no free radical trapping properties in a cell culture model of neurotoxicity (Hainsworth et al, 2008) and most probably acts at the neurovascular unit (Fisher et al, 2006) where brain penetration would not be a requirement for access to the site of drug action. Overall, these findings indicate that the site and mechanism of action of NXY-059 was not clearly understood in animal models at the time the agent was developed in clinical studies.…”
Section: Clinical Trial Development and Stair Criteriamentioning
confidence: 99%